2020
DOI: 10.1039/d0fo00855a
|View full text |Cite
|
Sign up to set email alerts
|

Health beneficial effects of resistant starch on diabetes and obesity via regulation of gut microbiota: a review

Abstract: Resistant starch (RS) is well known to prevent type 2 diabetes mellitus (T2DM) and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 165 publications
1
43
0
3
Order By: Relevance
“…Indeed, it is clear how feeding has great relevance in this transitional time point, highlighting these primary results. Although Ruminococcaceae are often associated with beneficial outcomes (Liu et al, 2020) based on their roles in butyrate metabolism in adults (Biddle et al, 2013), their presence in our cohort was not necessarily beneficial. Thus, the different and widely reported involvement of Bifidobacteriaceae in gut health remains a key factor to be considered in formula feeding.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, it is clear how feeding has great relevance in this transitional time point, highlighting these primary results. Although Ruminococcaceae are often associated with beneficial outcomes (Liu et al, 2020) based on their roles in butyrate metabolism in adults (Biddle et al, 2013), their presence in our cohort was not necessarily beneficial. Thus, the different and widely reported involvement of Bifidobacteriaceae in gut health remains a key factor to be considered in formula feeding.…”
Section: Discussionmentioning
confidence: 65%
“…Luo et al (2019) reported that a high soy isoflavone diet (450 mg/kg) can reduce the occludin concentration in high-fat-diet-induced obese rats [81]. There are previous reports stating the beneficial effects of resistant starch in preventing type 2 diabetes and obesity through improving gut barrier function [82]. While it is unclear why occludin concentration was reduced in our LS group, it can be understood that the effect of resistant starch and high equol levels in improving gut barrier function in the LSR group was considerably high.…”
Section: Discussionmentioning
confidence: 99%
“…The high plasma butyric acid concentration in the LR and LSR groups also proved this. Of all the SCFAs, butyrate has been studied most extensively for its role in nourishing the colonic mucosa and maintaining gut barrier function [82]. A meta-analysis indicated that in PCOS patients, abnormal SCFA metabolism was caused by disrupted gut microbiota, which is linked to insulin resistance and hyperandrogenemia [83].…”
Section: Discussionmentioning
confidence: 99%
“…Among the functional components, Kudzu starch is commonly used as a functional food to manage type 2 diabetes mellitus (T2DM). Kudzu starch contains a certain amount of resistant starch, which is a new type of dietary fiber frequently reported in recent studies, and a large number of studies have shown that resistant starch is an important part of daily food with significant hypoglycemic properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%